Association of lifestyle and flourishing during the COVID-19 pandemic in Japan - Shibata, Tomoyoshi; Yamaoka, Yui; Nawa, Nobutoshi; Nishimura, Hisaaki; Koyama, Yuna; Kuramochi, Jin; Fujiwara, Takeo (Frontiers in Psychology, 2024)
Introduction: COVID-19 have changed our lifestyle and little is known how our lifestyle associated with flourishing during COVID-19. This study examined the association between lifestyle, including sleep time, drinking, and smoking, and flourishing during the COVID-19 pandemic in Japan. Methods: We used the population-based study, Utsunomiya COVID-19 seROprevalence Neighborhood Association (U-CORONA) survey conducted in November 2021 to examine the association between lifestyle such as sleeping time, drinking and smoking, and flourishing (n = 473). Flourishing was assessed with the Flourishing index, a 10-item multidimensional scale with five domains. Multivariate linear regression analysis was performed adjusted for sex, age, income, and education. Results: We found that the flourishing index was significantly lower in the group that slept less than 6 h than in the group that slept 6–8 h (coef= -0.49, SE = 0.17, p <0.01). We also found that drinking once or several times/month and once or several times/week showed higher flourishing than those who almost never drink (coef= 0.57, SE = 0.19, p <0.01). Smoking was not associated with flourishing. Discussion: Sleep duration and drinking habit, but not smoking, may be important for flourishing during the COVID-19 pandemic.